An amorphous ZnO and oxygen vacancy modified nitrogen-doped carbon skeleton with lithiophilicity and ionic conductivity for stable lithium metal anodes. Issue 34 (11th August 2022) - Wang, Fei; Gao, Jingxia; Liu, Yong; Ren, Fengzhang
Abstract : The ZnO and oxygen vacancies modified nitrogen-doped 3D carbon skeleton with lithiophilicity and ionic conductivity can reduce local current density and show low ion concentration on the surface to induce uniform deposition of lithium. Abstract : Lithium metal is regarded as the most potential anode material for batteries with a high energy density, but is seriously hampered by the dead Li and Li dendrites generated during cycling. Appropriate control of the Li plating/stripping process is an effective strategy to alleviate these above two issues. Here, a ZnO and oxygen vacancy modified nitrogen-doped three-dimensional (3D) carbon skeleton is designed as a multifunctional host for stable Li metal anodes. The synergistic effect of the 3D structure with reduced local current density, lithiophilic nitrogen-doped sites and tiny amorphous ZnO with low nucleation barriers, and oxygen vacancies with high ion conductivity guide Li deposition. When used as an anode, the designed symmetric cell exhibits a long-term cycling duration over 1500 h with a low overpotential (16 mV) at 5 mA cm −2 and 5 mA h cm −2 . The full cell of MA-Zn-C-Li//LiFePO4 also exhibited superior cycling performance. This work provides a promising surface adjustment strategy with a difunctional host for high-performance Li metal batteries.